Discovering the Karoo: the genius loci of Compassberg, Nieu-Bethesda: Plant Research Centre and Landscape Interpretation Centre - Naude, Nerina (University of the Free State, 2020)
This dissertation is a proposal for a Landscape Interpretation Centre and Plant Research Centre at Compassberg in Nieu-Bethesda, Eastern Cape. The aim of the project is to assist the South African Centre of Social Science Research (CSSR) in protecting and researching the Karoo's biodiversity. In doing so, the project also aims to highlight the unique fauna and flora found at Compassberg that, for most, are undiscovered and undocumented. The focus of this dissertation came from a keen interest in the natural environment, more specifically, in the Karoo. The overarching aim of this proposal is to inspire a greater appreciation and knowledge for the natural landscape at Compassberg. To achieve this, it is necessary to consider the voice of the landscape and finding an appropriate architectural response that makes a meaningful contribution to the undiscovered layers of the Karoo. In this dissertation, the parameters of the research are set out by identifying the challenges and aims of the proposed design. A move towards exploring and grounding these aspects in research, analysis, theoretical review and interpretations was then made to conceptualise the ideas that drove the design. These concepts and formative ideas were then incorporated into an architectural design and technically documented proposal. Finally, evaluation of the dissertation was done through reflection and contemplation regarding the set challenges and aims
Dissertation (M.Arch. (Architecture))--University of the Free State, 2020
Keywords: Karoo's biodiversity; Landscape interpretation - Plant Research Centre; Genius loci of Compassberg - Nieu-Bethesda